Evaluation of occlusal groove patterns of mandibular first and second molars in an Indian population: A forensic anthropological study - Rashmi GS Phulari; Rajendrasinh Rathore; Mili D Takvani; Shivani Jain (Wolters Kluwer Medknow Publications, 2017)
Background: The study of dental morphological characteristics is important in anthropological research as it can provide information on the phylogenetic relationship between species, as well as variations and diversities within a population. Aims and Objectives: To determine the prevalence of six types of mandibular second molars in Gujarat state and the results can be used in both forensic anthropological researches and clinical aspects of dental sciences. Materials and Methods: This descriptive investigation was undertaken among 1000 students (13-25 years old) in high schools and dental institutes of Gujarat state. The students were selected by cluster sampling method and screened for the number of cusps and groove patterns of mandibular first and second molars. Gender and religion of the students were recorded on prepared forms. Statistical Analysis: It was done with the help of STATAIC-13 software. Descriptive statistics were used to summarize the data and Pearson's Chi-square test was used to check association between variables. Throughout the discussion, level of significance was set at 5%. Results and Conclusion: The high percentage of "+-"shaped groove pattern and low percentage of primitive "y-"shaped pattern in our study shows a tremendous evolutionary trend persisting in this population. The analysis of dental morphological traits is crucial in anthropological research as it can provide data on the phylogenetic relationship between species, as well as variations and diversities within a population.